Preparation, microstructural characterization, and selected mechanical properties of Ti-20Zr-2.5Mo and Ti-20Zr-7.5Mo used as biomaterial - Kuroda, Pedro Akira Bazaglia [UNESP] (2016)
Titanium is used in the biomedical field due to its mechanical strength/density, corrosion resistance, and biocompatibility. In this paper, the preparation, and the structural, microstructural, and mechanical characterization of Ti-20Zr-2.5Mo and Ti-20Zr-7.5Mo alloys are presented. The elements were melted into an arc furnace with an argon controlled atmosphere. To determine the amount of impurities present in each alloy, an analysis of the chemical composition was conducted using EDS. The samples were characterized by measurements of density, X-ray diffraction (with the diffractograms refined by the Rietveld method), and optical and scanning electron microscopy. The mechanical properties were evaluated using Vickers microhardness test and modulus of elasticity. The results showed that that α’/α” and α’'/β phases coexisted in both of the prepared alloys, respectively. The alloys have higher hardness than cp-Ti and their modulus of elasticity values are very close to the modulus values of cp-Ti.